PREVALENSI KEJADIAN ASTIGMATISME (MATA SILINDER) PADA MAHASISWA UNIVERSITAS MA CHUNG MALANG PADA BULAN JULI TAHUN 2024 Prevalence Of Astigmatism (Cylinder Eye) In Students Of Ma Chung University Malang In July 2024 - Hendra Yuda; Joko Irawan; Kukuh Mujiono (CV. ALIM'SPUBLISHING, 2024)
Astigmatism is a refractive disorder caused by uneven curvature of the cornea or lens, causing light not to focus on the retina. This study aims to measure the prevalence of astigmatism among students at Ma Chung University and identify the relationship between the duration and position of gadget use with astigmatism. The study method used a cross-sectional design involving 125 students aged 17–24 years. Data were collected through questionnaires and eye examinations using a Snellen chart and keratometer. The results showed that 38.4% of students had astigmatism. Most students (96.8%) used gadgets for more than 2 hours a day, and 91.2% used gadgets in a lying position. Using gadgets in this position and for long durations increases the risk of astigmatism. The conclusion of this study is that astigmatism is a significant problem among students. Implementation of the 20-20-20 rule and increasing outdoor activities are recommended for prevention. Routine eye examinations are also needed so that disorders can be detected and treated early.